Entrapment of a phage cocktail and cinnamaldehyde on sodium alginate emulsion-based films to fight food contamination by Escherichia coli and Salmonella Enteritidis - Alves, Diana Filipa Barros (2020)
Notwithstanding the implementation of good processing practices in food companies and appropriate washing of food products by the consumer, Salmonella and Escherichia coli outbreaks continue to occur. In this study, different combinations of bacteriophages (phages) and cinnamaldehyde (CNMA) were incorporated on sodium alginate emulsion-based films to impart them with antimicrobial activity towards S. Enteritidis and E. coli. Films were prepared by casting and they were characterized in terms of CNMA and/or phages loading, thickness, moisture content, water vapor permeability (WVP), swelling index (SW), chemical interactions by FTIR, surface morphology by SEM and antimicrobial performance. Results showed that phages incorporation was not compromised by CNMA as evidenced by their viability inside the films. Increasing CNMA concentration yielded formulations less heterogeneous and a higher amount of CNMA loaded. Films characterization revealed that, in general, phages incorporation did not introduce significant changes on films parameters while the presence of CNMA increased the roughness, thickness and swelling ability of films. Sodium alginate films incorporated with EC4 and Ï135 phages displayed antimicrobial activity against E. coli and S. Enteritidis, respectively, while CNMA empowered the films with activity against both species. Combination of both phages with the higher concentration of CNMA resulted in a synergic antimicrobial effect against E. coli and a facilitative effect against Salmonella. Overall, incorporation of EC4 and Ï135 phages together with CNMA on alginate emulsion-based films holds great potential to be further applied in food packaging to prevent food contamination.